Noninvasive screening test for detecting early stage lymphedema using follow‐up computed tomography imaging after cancer treatment and results of treatment with lymphaticovenular anastomosis. Issue 8 (16th June 2017) - Akita, Shinsuke; Ogata, Fusa; Manabe, Ichiro; Mitsuhashi, Akira; Nakamura, Rikiya; Yamaji, Yoshihisa; Kubota, Yoshitaka; Mitsukawa, Nobuyuki
Abstract : Background: Although early detection is valuable for secondary lymphedema treatment, existing screening tests are not popular. This study aimed to propose a novel method of screening lymphedema patients based on the thickness of the subcutaneous fat measured with perioperative computed tomography (CT) and present the results from evaluation of patients who underwent those examinations was performed. Method: The medical records of 96 gynecological cancer patients and 189 breast cancer patients, whose lymphatic function was assessed with indocyanine green lymphography, were reviewed. In gynecological cancer patients, the perioperative temporal subcutaneous fat thickness index (T‐SFTI) was calculated from presurgical and follow‐up CT data, and in breast cancer patients, the postoperative crosswise subcutaneous fat thickness index (C‐SFTI) was calculated. In lower extremity lymphedema patients, the effect of lymphaticovenular anastomosis (LVA) was also evaluated using T‐SFTI. Results: Perioperative T‐SFTI was assessed in 180 lower extremities, and it was significantly higher in 46 lymphatic dysfunction limbs (1.21 ± 0.08) than in 134 normal lymphatic function limbs (1.03 ± 0.08), ( P  < .01). Postoperative C‐SFTI was assessed in 53 upper extremity, and it was significantly higher in 11 lymphatic dysfunction limbs (1.31 ± 0.21) than in 42 normal lymphatic function limbs (1.01 ± 0.06), ( P  < .01). In lower extremity lymphedema patients, T‐SFTI improved significantly after planned conservative treatments and LVA ( P  = .04). Conclusion: Assessment of subcutaneous fat thickness using CT is useful for screening early stage lymphedema. If the efficacy of this method is validated, patients worldwide may be assessed using the same criterion.